Chinese Yellow Dust and Korean infant health. (August 2017) - Altindag, Duha T.; Baek, Deokrye; Mocan, Naci
Abstract: Naturally-occurring Yellow Dust outbreaks, which are produced by winds flowing to Korea from China and Mongolia, create air pollution. Although there is a seasonal pattern of this phenomenon, there exists substantial variation in its timing, strength, and location from year to year. To warn residents about air pollution in general, and about these dust storms in particular, Korean authorities issue different types of public alerts. Using birth certificate data on more than 1.5 million babies born between 2003 and 2011, we investigate the impact of air pollution, and the avoidance behavior triggered by pollution alerts on various birth outcomes. We show that air pollution rises during Yellow Dust outbreaks and that exposure to air pollution during pregnancy has a significant negative impact on birth weight, the gestation weeks of the baby, and the propensity of the baby being born low weight. Public alerts about air quality during pregnancy help mitigate the adverse effect of pollution on fetal health. The results provide evidence for the effectiveness of pollution alert systems in promoting public health. They also underline the importance of taking into account individuals' avoidance behavior when estimating the impact of air quality on birth outcomes. We show that when the preventive effect of public health warnings is not accounted for, the estimated relationship between air pollution and infant health is reduced by more than fifty percent. In summary, air pollution has a deteriorating impact on newborns' health, and public alerts that warn individuals about increased air pollution help alleviate the negative impact. Highlights: Yellow Dust is a weather phenomenon that originates in deserts of China and Mongolia. Easterly winds carry these dust particles to Korea, increasing the PM10 pollution. Exposure to these air pollutants during pregnancy reduces newborns' birth weight. Public health alerts help mitigate the adverse impact of pollution on infant health. Omitting public alerts leads to underestimates of pollution's impact on infant health.